PENGARUH PEMBIAYAAN MIKRO SYARIAH PADA BNI SYARIAH KCP KOLAKA TERHADAP OPTIMALISASI USAHA MIKRO, KECIL, DAN MENENGAH DI KECAMATAN KOLAKA KABUPATEN KOLAKA - Abdul Haris Nasution; Syawal Fitri (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
This study aims to determine Islamic banking on the optimization of micro, small and medium enterprises in Kolaka District, Kolaka Regency. Primary data was obtained from the results of a questionnaire of 20 respondents who received sharia microfinance at BNI Syariah KCP Kolaka. The formulation of the problem in this study is whether there is an influence of sharia microfinance in optimizing MSMEs in Kolaka sub-district, Kolaka district? This research method is carried out with a quantitative approach and the type of empirical research using field data obtained. The data collection instrument used a Likert scale measurement with data collection techniques in the form of a questionnaire/questionnaire and documentation. With data analysis techniques through the SPSS program namely validity, reliability, simple regression after that to find the effect of the two variables carried out by correlation test / t test (significant). This study was analyzed by the SPSS application program with. using simple linear regression test to see the effect between variables. The results of this study indicate that the variable Islamic microfinance has a significant effect in optimizing MSMEs in Kolaka District, Kolaka Regency.